Shifts in Australia's Migration Policy Strategy 2023-2025: Promoting Economic Growth and The Impact on the Labor Market - Handayani, Riska Sri; Yuliatiningtyas, Solikhah (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Australia, as one of the primary destinations for immigrants, has experienced significant shifts in migration policy over recent years. This policy, which increasingly opens up opportunities for foreign workers, aligns with the growing demand for labor in the post-COVID-19 pandemic era. This study aims to analyze changes in Australia's migration policy during the period 2023-2025 and its impact on the labor market and the national economy. Based on statistical data and international reports, migration policies focusing on skilled labor in critical sectors such as agriculture, manufacturing, and healthcare are projected to make a significant contribution to Australia's Gross Domestic Product (GDP). Furthermore, this research adopts a theoretical approach by utilizing the Resource Dependence Theory to understand the relationship between migration policy and Australia’s dependence on foreign labor. The findings suggest that despite several challenges, this migration policy is expected to strengthen Australia’s position in the global market and create greater economic opportunities.